Adverse drug reactions associated with six commonly used antiepileptic drugs in southern China from 2003 to 2015 - Yanru Du; Jiahe Lin; Jingzan Shen; Siqi Ding; Mengqian Ye; Li Wang; Yi Wang; Xinshi Wang; Niange Xia; Rongyuan Zheng; Hong Chen; Huiqin Xu (BMC, 2019)
Abstract Background This active, open observational study aimed to investigate adverse drug reactions (ADRs) associated with six commonly used antiepileptic drugs (AEDs) in southern Chinese outpatients with epilepsy from 2003 to 2015. Methods The Wenzhou Epilepsy Follow-Up Registry Database (WEFURD) was established by a single epilepsy center in China in January 2003 to record AED efficacy and the associated ADRs by registered outpatients diagnosed with epilepsy. We reviewed the data of outpatients who had only taken one or more of six commonly used AEDs, namely, carbamazepine (CBZ), valproate (VPA), lamotrigine (LTG), oxcarbazepine (OXC), topiramate (TPM) and levetiracetam (LEV), and were registered in the WEFURD between 2003 and 2015. We evaluated the ADRs caused by the single or combined use of the above six specific AEDs based on the WHO-UMC scale. The data of the ADRs were categorized by age, sex, number of AEDs related to ADRs, medications, seriousness of ADRs, causality levels of the WHO-UMC scale and system organ class (SOC). The unit of analysis was one ADR. Results A total of 3069 epilepsy outpatients (1807 outpatients with 5049 eligible ADRs and 1262 outpatients without ADRs) were included. The overall ADR rate was 58.88% (1807/3069). An average of 2.79 ADRs (5049/1807) occurred per patient with an ADR; 53.8% of the 5049 ADRs were recorded in females, and 50.4% were caused by monotherapy. Of the ADRs, 10.6% (537/5049) were severe adverse reactions (SARs), including 34 serious adverse effects (SAEs). The SAR rates caused by one, two and three or more AEDs were 9.9, 10.0 and 19.6%, respectively (p <  0.001). Eighteen SOC categories were identified, and the top three were psychiatric disorders (1633/5049, 32.3%), neurological disorders (1222/5049, 24.2%) and gastrointestinal disorders (564/5049, 11.2%). Of the 537 SARs, skin and appendage disorders accounted for 24.4% (131/537). Among the 34 SAEs, serious allergies, fetal malformations, renal calculus and pancreatitis accounted for the majority. Conclusions Our findings suggest that clinicians should pay attention to psychiatric ADRs and be alert for SARs, especially when three or more AEDs are used together. Moreover, active surveillance might provide another method of pharmacovigilance in China.